The Politics of Religion in South and Southeast Asia - Ahmed, Ishtiaq (Routledge contemporary Asia series, 2011)
The notion of a 'politics of religion' refers to the increasing role that religion plays in the politics of the contemporary world. This book presents comparative country case studies on the politics of religion in South and South Asia, including India, Pakistan and Indonesia